Enjoying the golden years: social participation and life satisfaction among Chinese older adults - Wu, Min; Yang, Dan; Tian, Yihao (Frontiers in Public Health, 2024)
Older adults commonly face the risk of social isolation, which poses a significant threat to their quality of life. This study explores the association between social participation and the life satisfaction of older Chinese adults, based on data from the 2018 China Health and Retirement Longitudinal Study. The results indicate that social participation has a significant positive association with older adults' life satisfaction, and with an increase in the diversity of social activities, the positive association with older adults' life satisfaction becomes even more pronounced. Through mediation analysis, this study revealed that social participation is positively correlated with older adults' life satisfaction, mediated by reductions in feelings of loneliness and improvements in health levels. Further analysis showed that social participation had a greater positive association with the rural older adults and those lacking family companionship. This study provides evidence for enhancing life satisfaction among older adults and highlights the importance of diversity in social participation.